Predicting differentiated developmental trajectories of prosocial behavior: A 12-year longitudinal study of children facing early risks and vulnerabilities. (July 2021) - Shi, Qinxin; Ettekal, Idean; Liew, Jeffrey; Woltering, Steven
The current study examined the heterogeneity in the development of school-based prosocial behavior from Grades 1 to 12 and the role of multiple early childhood antecedents in predicting heterogeneous developmental trajectories of prosocial behavior in a sample of 784 children facing early risks and vulnerabilities (predominantly from low-income families and academically at risk; 52.6% male). In alignment with the risk and resilience framework, antecedents consisted of risk and protective factors from both individual (i.e., ego-resilient personality, behavior problems, intelligence, academic performance, gender, and ethnicity) and contextual domains (i.e., maternal support and responsiveness, family socioeconomic adversity, teacher–child warmth and conflict, and peer acceptance and rejection). We identified four distinct prosocial trajectories including a high-stable (52.5%), high-desisting (15%), moderate-increasing (20.6%), and low-stable class (11.9%). Results revealed that the low-stable, high-desisting, and moderate-increasing classes were associated with lower ego resiliency, higher behavior problems, lower teacher–child warmth, higher teacher–child conflict, and peer rejection in early childhood, compared to the high-stable group. Boys and African Americans were more likely to be in the low-stable, high-desisting, and moderate-increasing classes. Individual characteristics such as ego-resilient personality and contextual influences such as teacher–child warmth served as common protective antecedents. Interestingly, teacher–child conflict served as a unique predictor for the high-desisting class, and behavior problems and peer rejection served as unique predictors for the low-stable class.